The Wicked Utopia: Artistic Creation for Indigenous-Inspired Utopian Thinking - Mao, Yue (author) (2018)
This project investigated into the only indigenous people in Europe, the Sami people in northern Scandinavia, explored the possibility to transfer their knowledge into a new Utopian thinking. Instead of a concrete urban planning or design, this project is designated to be a meta process of thinking pattern, for which inter-subjective artistic creation plays an important role. It involves a in-depth historical research into indigenous thinking and Utopian thinking, concluded by the mentality and image constructing skills and implemented into two Utopian scenarios in Kiruna (Sweden) and Delft (the Netherlands).